2017
DOI: 10.1016/j.jneumeth.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and validation of a split belt treadmill for measuring hindlimb ground-reaction forces in able-bodied and spinalized felines

Abstract: BACKGROUND The measurement of ground reaction forces (GRFs) in animals trained to locomote on a treadmill after spinal cord injury (SCI) could prove valuable for evaluating training outcomes; however, quantitative measures of the GRFs in spinal felines are limited. NEW METHOD A split belt treadmill was designed and constructed to measure the GRFs of feline hindlimbs during stepping. The treadmill consists of two independent treadmill assemblies, each mounted on a force plate. The design allows measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…GRF, inclinometer and accelerometer sensor data were acquired using LabVIEW software (1000 s/s), which was filtered offline using a 2 nd order Butterworth zero-phase low-pass filter (inclinometer used a 20 Hz cutoff; load cells and accelerometer used a 200 Hz cutoff). Load cell cut-off frequencies are similar to commercial software used in animal research settings (Dimiskovski et al, 2017) and power spectral analyses revealed that a majority of sensor data signals fell below 1 Hz and 25 Hz for the inclinometer and accelerometer/load cells respectively. All sensor data were normalized to a period found in the 200 ms time window prior to tilt start for each trial.…”
Section: Methodsmentioning
confidence: 92%
“…GRF, inclinometer and accelerometer sensor data were acquired using LabVIEW software (1000 s/s), which was filtered offline using a 2 nd order Butterworth zero-phase low-pass filter (inclinometer used a 20 Hz cutoff; load cells and accelerometer used a 200 Hz cutoff). Load cell cut-off frequencies are similar to commercial software used in animal research settings (Dimiskovski et al, 2017) and power spectral analyses revealed that a majority of sensor data signals fell below 1 Hz and 25 Hz for the inclinometer and accelerometer/load cells respectively. All sensor data were normalized to a period found in the 200 ms time window prior to tilt start for each trial.…”
Section: Methodsmentioning
confidence: 92%
“…Kinematic analysis shows similar gait recovery with BDNF or treadmill training in spinalized cats. The analysis of the GRFs also showed results similar to trained animals in terms of weight support [20] and superior to non-treated animals. The BDNF treated cats were capable of performing some full weight-bearing stepping during locomotion at medium speed (0.4 m/s).…”
Section: A Advantages Of Intrathecal Bdnf Delivery Via Implantable Mini-pumpmentioning
confidence: 56%
“…Ground reaction forces (GRFs) were collected in six cats (two Controls and four BDNFs) during locomotion trials 5 weeks post-transection using an instrumented split belt treadmill where each belt motor assembly (left and right) was mounted on a Kistler force plate (Kistler Instrument Corp., Winterhur, SUI) [20]. The vertical components of the GRFs (Fz) were evaluated during locomotion at 0.4 m/s to estimate the animals' ability to weight support.…”
Section: E Ground Reaction Forces Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Spinally injured cats have shown altered limb loading that contributes to a 55% reduction in vertical ground reaction forces (GRFs) compared with intact felines. 8 Similar reductions are also evident in hindlimb propulsive and braking forces in rats after spinal injury, 9 resulting in limited locomotion. 10 A paucity of studies, however, has explored the impact of iSCI on force production during overground walking in humans.…”
Section: Introductionmentioning
confidence: 78%